"We don't always get it right": Coaches' perspectives on supporting injured athletes. Issue 3 (2nd September 2021) - Maurice, Stefanee; Voelker, Dana K.; Kuklick, Clayton; Byrd, Megan
ABSTRACT: Research with injured athletes highlights a considerable lack of support from coaches during rehabilitation, yet coaches' perspectives are rarely studied. Knowledge critical to effective coaching has been examined, but not within the context of injury. Thirteen coaches were interviewed regarding (1) perceptions of their role during rehabilitation, (2) use of International Sport Coaching Framework (ISCF) knowledge types to support injured athletes, and (3) perceived barriers to providing support. Data were analysed using deductive and focused coding based on the ISCF framework. Coaches reported increasing frequency of contact with athletes during rehabilitation and using interpersonal knowledge to learn about their athletes. Athletes' welfare and longterm health were important considerations for coaches when providing support. Coaches reported athletes could be significant barriers to providing support, in addition to policy and resource constraints. The results can teach coaches and coaching educators to identify effective uses of coaching knowledge to improve athletes' injury rehabilitation.